PERANCANGAN SISTEM APLIKASI E-OFFICE BERBASIS WEB PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN MUARO JAMBI - Jeffri, Muhammad; Kurniawansyah, Kevin (LPPM Universitas Muhammadiyah Jambi, 2023)
The Department of Population and Civil Registration of Muaro Jambi Regency is the executor of government affairs in the field of population administration, in general for office administration purposes, such as archiving documentation and correspondence management. In general, the work process in local government agencies is inseparable from various problems, such as work management that is not good and neat, or other information management processes that are deemed inaccurate. The results of the study show that the management of incoming and outgoing letter archival data still uses a manual system, namely recording in an agenda book and then placing the letters in a special mail archive cupboard without any backup data. The management of letter archives at the Population and Civil Registration Office of the Muaro Jambi Regency is carried out by the general and personnel sub-divisions. The facilities available at this time are an agenda book to record incoming and outgoing mail data, then a cupboard as a means of storing archival data of incoming and outgoing letters. The solution proposed by the author is to design and build a web-based E-Office application system for archiving incoming and outgoing mail data. In developing the system the author uses the method (Waterfall) and UML design along with supporting applications for making the application developed using the java programming language, php, and the MYSQL database. The results of making this application can be used by the Muaro Jambi Regency Population and Civil Registration Service, especially as a medium for completing documents and other official letters.